Diagnostic Values of Laser Fluorescence Device with Other Techniques in Occlusal Caries Detection - M. Biria; M. Moshfeghi; A. Akbarzadeh Baghban; A. Chehresaz (Tehran University of Medical Sciences, 2009)
Objective: The aim of the present study was to compare the performance of laser fluorescence (LF) method with other conventional diagnostic techniques in detection of small occlusal caries in permanent teeth. Materials and Methods: Prior to this in vitro diagnostic study, a pilot study assessed intra- examiner reliability and reproducibility. The occlusal surfaces of 90 extracted human premolars were examined with four diagnostic methods: probing, visual inspection, bitewing (BW) radiographs, and LF. The teeth were then sectioned for the purpose of histological examination. The data were analyzed using SPSS 15 software, and sensitivity, specificity and other diagnostic criteria of the techniques were calculated. Results: The intra-examiner reproducibility for probing and also radiographic techniques was 100%. The corresponded figure for LF (88%) was more than visual inspection (82%). The highest level of validity of the examiner turned out to be in probing technique (76.9%). Sensitivity of visual inspection, probing, and LF methods was 54.5% and that of BW radiography was 27.5%. Specificity and efficiency of LF method were 84.8% and 81.1%, respectively. Probing and visual inspection showed the highest specificity (97.5% and 94.9, respectively) and efficiency (92.2% and 90%, respectively) among the methods. Conclusion: Specificity and efficiency of LF method were lower compared to those of other methods. Among all the investigated methods, the most efficient methods in the diagnosis of small occlusal caries in permanent teeth were probing and visual inspection, respectively.